2017
DOI: 10.1038/s41598-017-08817-x
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B reverses doxorubicin resistance through inhibiting P-glycoprotein and promoting proteasome-mediated degradation of survivin

Abstract: Acquired drug resistance poses a great challenge in cancer therapy. Drug efflux and anti-apoptotic processes are the most two common mechanisms that confer cancer drug resistance. In this study, we found that Schisandrin B (Sch B), one of the major dibenzocyclooctadiene derivatives extracted from Chinese herbal medicine Schisandrae Chinensis Fructus, could significantly enhance the sensitivity of doxorubicin (DOX)-resistant breast cancer and ovarian cancer cells to DOX. Our results showed that Sch B increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…P-gp inhibitors or substrates can enter the cell from the extracellular compartment to the cytosol via filtration, simple diffusion, or specialized transport. The first step of substrate efflux is the combination of P-gp and the substrates promoted by ATPbinding and hydrolys (Wang et al, 2017a)is. Vanadate trapping and photo-cleavage experiments showed that P-gp contains two active ATPase sites, but only one ATP is hydrolyzed at a time (Hrycyna et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…P-gp inhibitors or substrates can enter the cell from the extracellular compartment to the cytosol via filtration, simple diffusion, or specialized transport. The first step of substrate efflux is the combination of P-gp and the substrates promoted by ATPbinding and hydrolys (Wang et al, 2017a)is. Vanadate trapping and photo-cleavage experiments showed that P-gp contains two active ATPase sites, but only one ATP is hydrolyzed at a time (Hrycyna et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 Various natural products have been shown to be excellent and reliable sources for pharmaceutical development and to be a useful and effective approach for MDR therapies, such as Schisandrin B and annonaceous acetogenins. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, various other studies have reported that miR-21-5p was associated with DPP resistance of gastric cancer cells ( 47 , 49 ). Furthermore, the increased resistance to DOX was not entirely due to the elevation of miR-21-5p, and is probably regulated by additional signaling pathways, including the inhibition of P-glycoprotein expression and activity, or via AKT-mediated upregulation of multidrug resistance-associated protein 1 ( 50 , 51 ). All of the above suggests that the mechanism of drug resistance is highly complex, while it is indicated that miR-21-5p may have an important role in the multidrug resistance of cancer cells.…”
Section: Discussionmentioning
confidence: 99%